Polychromatic Source Excitable and Enhanced Green Photoluminescence of ZnO Nanoparticles Dispersed in High Molecular Weight Polymer Matrix - Mikrajuddin Abdullah (Journal of Mathematical and Fundamental Sciences, 2003)
Composite of zinc oxide (ZnO) nanoparticles in polyethylene glycol (PEG) has been produced by mixing the as prepared ZnO colloid with a solution of PEG in ethanol. ZnO colloid was produced by hydrolizing zinc acetate in ethanol solution. The produced composite exhibits a wide band excitation spectra compared to ZnO colloid to allow the excitation using a wide range excitation wavelength for producing high green luminescence intensity. Since ZnO nanoparticles were trapped in a matrix of polymer (solid phase) no further growing as well as agglomeration process took place (as observed in ZnO colloid) so that the shape and positions of excitation and luminescence spectra were time independent. Heating the prepared composite results an increase in the luminescence intensity due the increase in the ZnO nanoparticles concentration in the heated composites.